Cell‐Free Protein Synthesis and Its Perspectives for Assembling Cells from the Bottom‐Up. Issue 6 (4th February 2019) - Kai, Lei; Schwille, Petra
Abstract: The underlying idea of synthetic biology is that biological reactions/modules/systems can be precisely engineered and controlled toward desired products. Numerous efforts in the past decades in deciphering the complexity of biological systems in vivo have led to a variety of tools for synthetic biology, especially based on recombinant DNA. However, one generic limitation of all living systems is that the vast majority of energy input is dedicated to maintain the system as a whole, rather than the small part of interest. Cell‐free synthetic biology is aiming at exactly this fundamental limitation, providing the next level of flexibility for engineering and designing biological systems in vitro. New technology has continuously inspired cell‐free biology and extended its applications, including gene circuits, spatiotemporally controlled pathways, coactivated catalysts systems, and rationally designed multienzyme pathways, in particular, minimal cell construction. In the context of this special issue, discussing work being carried out in the "MaxSynBio" consortium, the advances in characterizing stochasticity and dynamics of cell‐free protein synthesis within cell‐sized compartments, as well as the molecular crowding effect, are discussed. The organization of spatial heterogeneity is the key prerequisite for achieving hierarchy and stepwise assembly of minimal cells from the bottom‐up. Abstract : Cell‐free protein synthesis is an emerging tool for synthetic biology, particularly bottom‐up assembly of minimal cells . Shifts toward quantitatively characterization of cell‐free protein synthesis systems allow for the design of modular systems for hierarchy and stepwise assembly minimal cell systems. In addition, stochasticity and molecular crowding should be considered when designing such minimal cellular systems.